Doing research with children : a practical guide - Greig, Anne (Anne D.); Taylor, Jayne, 1957-; MacKay, Tommy (London ; Los Angeles, Calif. : SAGE, 2013)
"The Third Edition of Doing Research with Children is practical introduction to the process of designing, doing and writing up research with children and young people. At the center is a commitment to engaging with children and young people as active research participants rather than as passive subjects. In this new edition, you'll find up to date information on the fast-changing political and ethical debates around research with children and young people as well as guidance on how to carry out research yourself. Divided into three sections, the new edition covers: The main theories and approaches of research with children and young people ; Expanded guidance on research ethics ; Techniques for conduction both qualitative and quantitative research ; More on analyzing your research ; A brand new chapter on communicating your research findings. This is a must-have guide for students and practitioners who are engaging in research with children and young people."--Publisher's website.
Part 1: The special nature of children in research - Theories and approaches. Introduction to Research and Children and Young People: A Special Relationship ; Theory for Research and Practice with Children and Young People ; Theoretical Frameworks. -- Part 2: Doing research with children and young people - reviewing, designing and conducting research with children. Evaluating Research with Children and Young People ; Designing and Doing Research with Children and Young People: The Importance of Questions ; Quantitative Research with Children and Young People: Key Concepts ; Quantitative Research with Children and Young People: Data Collection ; Designing and Doing Qualitative Research with Children and Young People ; Consultation and Participation with Children and Young People in Research ; Ethics of Doing Research with Children and Young People ; Communicating Research ; Themes and Perspectives.
Previous ed.: 2007.
Includes bibliographical references and indexes
Keywords: Children -- Research -- Methodology; Children -- Research -- Moral and ethical aspects